PENERAPAN STRATEGI PEMBELAJARAN OTENTIK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII4 SMP NEGERI 17 PEKANBARU - Ramadhan, Puteri Nurul; ', Zuhri D; Hutapea, Nahor Murani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and improve the student?s mathematics learning outcomes through the implementation of Authentic Learning Strategy. The type of research is the Classroom Action Research with two cycles. The research was conducted in student of grade VIII4 SMP N 17 Pekanbaru in the first semester of the academic year 2016/2017 with the subject of as many as 38 students. The research instrument are consists of learning devices and instrument data collectors. Learning device used in this research are consists of the Syllabus, Lesson plan and Student work sheet. The instrument data collector used in this research is consists of the observation sheet and math test. Technique of data analysis is analysis of narrative descriptive and analysis of statistical descriptive. Based on the result of the research show that, there have been improvements on the learning proses and improvement on the student?s mathematics learning outcomes after applying the Strategy of Authentic Learning.                                                                                                                          Keywords: Authentic Learning Strategy, learning process, students learning outcomes